2009
DOI: 10.1557/jmr.2009.0316
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polypyrrole/TiO2 nanocomposite and its photocatalytic activity under visible light irradiation

Abstract: A simple and convenient method for preparing visible light response photocatalyst polypyrrole/TiO 2 (PPy/TiO 2 ) nanocomposite was developed. The products were characterized by x-ray diffraction, transmission electron microscopy, atomic force microscopy, ultraviolet-visible, and Fourier transform infrared techniques. The results indicated that the nanohybrid was composed of anatase TiO 2 and PPy and exhibited an enhanced visible light-capturing ability. Average diameters of TiO 2 and PPy/TiO 2 were 18 and 35 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…It can indicate that the polymerization of PPy can alleviate the aggregation of M‐TiO 2 nanoparticles. Compared with other reports , the PPy/TiO 2 possesses a better dispersity. It must be due to the modification of silane coupling agent and the merits of reverse microemulsion polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can indicate that the polymerization of PPy can alleviate the aggregation of M‐TiO 2 nanoparticles. Compared with other reports , the PPy/TiO 2 possesses a better dispersity. It must be due to the modification of silane coupling agent and the merits of reverse microemulsion polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent years, conductive polymers with conjugated double‐bond, has received much attention due to its metallic like conductivity. These conductive polymers possess a relatively narrow band gap and can enable an efficient separation of charge, which is important for photocatalytic application . Therefore, many researchers have focused on the preparation of TiO 2 /conductive polymer composites to overcome the shortcomings of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…When visible light impinges on the composite surface, electrons are promoted from HOMO to LUMO of PPy (which has a reported band gap energy of 2.2 eV) [ 56 ], generating holes in the PPy chain (h+), electrons in the LUMO (−1.15 V versus NHE) [ 56 ], travel through PPy chains to conduction band (CB), (−0.23 V versus NHE) [ 57 ], of inorganic material, which can react with oxygen solved in the aqueous phase initiating photo-reduction. On the other hand, electrons in the valence band (VB) of inorganic material travels to h+ in the HOMO of PPy, generating a hole in the VB in the inorganic material.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structure and functional groups of the PPy/TiO 2 composites have been investigated using the FTIR technique. 28,42,46,57 The analysis of pure PPy conducted by Li et al 60 showed absorption bands characteristic of the polymer (Figure 7 (a)). The peaks at 3400, 1548, 1450, 1045 and 790 cm −1 correspond to N–H, C=C (in pyrrole ring), C–N, C–O–C, and C–C stretching vibrations, respectively.…”
Section: Properties Of Ppy/tio2 Compositesmentioning
confidence: 99%